2021
DOI: 10.3390/catal11080917
|View full text |Cite
|
Sign up to set email alerts
|

Measures to Reduce the N2O Formation at Perovskite-Based Lean NOx Trap Catalysts under Lean Conditions

Abstract: The net oxidising atmosphere of lean burn engines requires a special after-treatment catalyst for NOx removal from the exhaust gas. Lean NOx traps (LNT) are such kind of catalysts. To increase the efficiency of LNTs at low temperatures platinised perovskite-based infiltration composites La0.5Sr0.5Fe1-xMxO3-δ/Al2O3 with M = Nb, Ti, Zr have been developed. In general, platinum based LNT catalysts show an undesired, hazardous formation of N2O in the lean operation mode due to a competing C3H6-selective catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A number of alternatives have been proposed, such as perovskites. Ecker et al 254,255 synthesized a platinized p e r o v s k i t e -b a s e d i n fi l t r a t i o n c o m p o s i t e P t / La 0.5 Sr 0.5 Fe 0.5 Ti 0.5 O 3 /Al 2 O 3 , but it was observed that at lower temperatures the competing reactions with C 3 H 6 -SCR resulted in a dramatic increase in N 2 O. This catalyst was further coated with Rh, and this led to an increase in NO x storage capacity (NSC), although no decrease in N 2 O emissions was observed within a temperature range of 300−450 °C.…”
Section: Hc-scrmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of alternatives have been proposed, such as perovskites. Ecker et al 254,255 synthesized a platinized p e r o v s k i t e -b a s e d i n fi l t r a t i o n c o m p o s i t e P t / La 0.5 Sr 0.5 Fe 0.5 Ti 0.5 O 3 /Al 2 O 3 , but it was observed that at lower temperatures the competing reactions with C 3 H 6 -SCR resulted in a dramatic increase in N 2 O. This catalyst was further coated with Rh, and this led to an increase in NO x storage capacity (NSC), although no decrease in N 2 O emissions was observed within a temperature range of 300−450 °C.…”
Section: Hc-scrmentioning
confidence: 99%
“…A number of alternatives have been proposed, such as perovskites. Ecker et al 254,255 Albaladejo-Fuentes et al 256 studied the BaTi 0.8 Cu 0.2 O 3 catalyst and observed that BaO generated on the catalyst by decomposition of Ba 2 TiO 4 is essential in the NO x storage process. At temperatures <350 °C, NO adsorption leads to formation of nitrites on the catalyst, and at temperatures >350 °C, NO oxidation occurs and promotes NO 2 generation and nitrate formation.…”
Section: Hc-scrmentioning
confidence: 99%